DOP29 Pregnancy outcomes in IBD patients treated with vedolizumab, anti-TNF, or conventional therapy. (25th January 2019) - Moens, A; van der Woude, C; Julsgaard, M; Sebastian, S; Arebi, N; Alzinaty, M; Humblet, E; Kok, K B; Sheridan, J; Gilletta De Saint-Joseph, C; Nancey, S; Rahier, J-F; et al.
Abstract: Background: Women with inflammatory bowel diseases (IBD) often receive biologicals during pregnancy to maintain disease remission prior to conception and throughout pregnancy. However, data on vedolizumab exposed pregnancies (VDZE) are scarce. Methods: This retrospective multi-centre observational study assessed outcomes of VDZE pregnancies in IBD patients (group A). European gastroenterologists were asked to report all VDZE pregnancies. Details of underlying IBD, pre- and postnatal outcomes were collected. Results were compared with anti-TNF exposed (TNFE, group B) or both immunomodulatory and biologic unexposed (IBU, group C) pregnancies. The control groups were prospectively enrolled from two separate centres. Results: Group A included 86 pregnancies in 81 women [53% Crohn's disease (CD), 70 live births] from 31 centres in 11 countries. Groups were comparable regarding baseline characteristics though group A included more women with ileocolonic CD and perianal involvement. At conception 35% of VDZE women had active disease, 17% were on steroids and 20% on immunomodulators. Also, 54% previously failed two biologicals. Group B and C included 186 pregnancies in 155 women and 185 pregnancies in 164 women respectively (83% vs. 55% CD, 162 vs. 163 live births). Controls had less active disease at conception (B:16%, C:24%) and fewer were taking steroids (B: 8%, C: 14%). More miscarriages were seen in group A compared with B (16% vs. 13%, p = 0.46) and C (16% vs. 8%, p = 0.03). However, after excluding patients with reported active disease in pregnancy, the number of miscarriages was similar in group A compared with B (14% vs. 14%, p = 1.0) and C (14% vs. 12%, p = 0.80). Neonatal outcomes are displayed in Table 1. In live-born infants, median gestational age and birth weight were similar between groups. Also median Apgar score at birth was numerically equal in all groups. The number of premature born infants was not significantly different between groups nor was the amount of reported congenital anomalies. The percentages of breastfed children were similar in all groups. During the first year of life, no malignancies were reported and the infants' infection risk did not significantly differ between groups. Conclusions: VDZE pregnancies were associated with more miscarriages; however, active disease in pregnancy rather than drug effect seems to have been the driver of this adverse pregnancy outcome, since no significant difference was observed after exclusion of patients with reported active disease. Still, larger prospective studies are needed for confirmation.